Patients’ education as a factor for arterial hypertension effective control – NOCTURNE Program - A. M. Kalinina; R. G. Oganov; D. V. Nebieridze (Кардиоваскулярная терапия и профилактика)
Aim. To assess effectiveness of Health School for arterial hypertension (AH) patients in NOCTURNE Program. Material and methods. An open, multi-center, prospective study was performed in 14 Russian regions, involving 140 primary health doctors and 1195 mild-to-moderate AH patients. The authors studied real-world clinical practice perspectives of total cardiovascular risk modification by pharmaceutical treatment regimen modification – administration of combined agent Noliprel®, once per day, and main risk factors (RF) control – educating patients at Health School. Total follow-up period lasted for 48 weeks. Results. In total, 66.5% of the participants had Stage II AH, 32.5% – Stage I AH; 78.3% were overweight (OW); 21.2% were smokers; 76.0% had increased stress levels; 66.3% had hypercholesterolemia (HCH). Follow-up was completed by 83.4% of the patients (n=997). During the follow-up period (mean duration 39.4±12.1 weeks), 85.1% of participants continued to take the medication. The treatment was associated with decrease in prevalence of OW (from 79.0% to 70.2%), smoking (from 21.6% to 14.6%), increased stress levels (from 81.0% to 71.0%), and HCH (from 65.9% to 49.2%). More than a half of the patients (53.9%) demonstrated decrease in total cardiovascular risk by SCORE scale. In the whole group, the total risk decreased from 2.5% to 1.3%. Conclusion. Real-world reduction of fatal cardiovascular disease total risk was confirmed. It was achieved by combination of complex therapeutic and preventive measures: optimal medication therapy regimen and nonpharmaceutical RF correction during patients’ education at Health School.